The Impact of Banking Services Marketing Mix on Customer Loyalty Case Study of Private Banks in Kurdistan - Iraq - اىٍػرس اىٍفاغػ أُؿ مضٍػ زْ٘ؽ اىطاج ضفَ٘; اىٍػرس اىٍفاغػ نِان غ٘فٕ اىفاٗؼ; اىٍػرس اىٍفاغػ غػي ضاةٔر اىؽاشػي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aim of this study is to investigate the elements of banking marketing mix in private banks in Kurdistan - Iraq, and the role of these factors in attracting customers from the market and encourage them to deal with these banks. Since the elements of marketing mix are considered as the most important factors that influence the customer loyalty, which requires the bank management to have an attention on the marketing of bank services in well-organized manner. Therefore, according to our questionnaire process and data analysis, the results indicate that customer loyalty correlates positively with product quality, Price, and place; while promotion, people, process of operations and physical environment has no correlation with customer loyalty.